HUBUNGAN PENGETAHUAN, SIKAP DAN PERILAKU DENGAN PENERAPAN KESELAMATAN DAN KESEHATAN KERJA NELAYAN DI PELABUHAN KOTA AGUNG TAHUN 2024 - Seroja, Estrelitha Maytari; Hasan, Amrul; Trigunarso, Sri Indra (NHM PRESS, 2024)
Occupational Safety and Health (K3) is a field of science related to the health, safety, and welfare of humans working in an institution or project location. The existence of occupational safety and health for workers is very important to anticipate and reduce the number of work accidents and occupational diseases as well as to protect workers, the government issued Law on Manpower No. 13 of 2003 Article 86 Paragraphs 1 and 2 which states